2002
DOI: 10.1128/cmr.15.3.439-464.2002
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Kaposi's Sarcoma-Associated Herpesvirus, or Human Herpesvirus 8, Diseases

Abstract: Human herpesvirus 8 (HHV-8), also known as Kaposi's sarcoma-associated herpesvirus (KSHV), discovered in 1994, is a human rhadinovirus (gamma-2 herpesvirus). Unlike other human herpesviruses (herpes simplex virus, Epstein-Barr virus, varicella-zoster virus, cytomegalovirus, HHV-6, and HHV-7), it is not widespread in the general population and has many unique proteins. HHV-8 is strongly associated with all subtypes of Kaposi's sarcoma (KS), multicentric Castleman's disease, and a rare form of B-cell lymphoma, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
188
0
19

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(213 citation statements)
references
References 277 publications
(274 reference statements)
6
188
0
19
Order By: Relevance
“…Possible causes of such associations are outlined in a number of reviews [6,10,12,29] and reports relating to the specific entities, that is, Kaposi's sarcoma [9,30], PNP [31], POEMS [29], and lymphoma [30,[32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible causes of such associations are outlined in a number of reviews [6,10,12,29] and reports relating to the specific entities, that is, Kaposi's sarcoma [9,30], PNP [31], POEMS [29], and lymphoma [30,[32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…A number of excellent reviews are available and give general oversight [3][4][5][6][7][8][9], focus on pathogenesis [4,10], pathological features [11,12], clinical presentation in HIV Ϫ [13] and HIV ϩ [14,15] patients, and management aspects [8,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…13,38 PEL cells are always infected with a transforming human g herpes virus (HHV) called Kaposi's sarcoma herpes virus (KSHV/HHV8) and often co-infected with EBV. 41 These cells, which have a latency I phenotype, as well as EBV(À) PEL cells are very sensitive to nutlin-3-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A possible source of nonsexual horizontal transmission (e.g., through saliva) was suggested by a study that analyzed KSHV transmission in children before puberty (38). KSHV transmission by injection drug use was rare among drug users in Amsterdam (39), but another study demonstrated that KSHV seropositivity increased in association with injection drug use (40).…”
Section: Discussionmentioning
confidence: 99%